1973
DOI: 10.1346/ccmn.1973.0210607
|View full text |Cite
|
Sign up to set email alerts
|

An Ultraviolet Spectroscopic Method for Monitoring Surface Acidity of Clay Minerals under Varying Water Content

Abstract: The ability of a clay mineral surface to function as an acid is not represented by bulk pH measurements. A method using u.v. analysis and organic indicators has been developed to monitor surface acidity. The u.v. organic indicator method enables sensitive in situ quantification of surface-induced protonation in wet or dry clay systems. The clay preparation procedure used yields reproducible acidic behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…16,18,30 The peak at 371 nm may also be contributed by phenazine. 31 Hence, from the UV-Vis and FTIR results, case (A) samples should be composed of the phenazine-like AN oligomers with some substituted quinones. 14,16,18,30 For case (B), the shape of the spectrum is similar to that obtained from case (A), except that a shifted band at 361 nm (from 371 nm) and a weak broad band B614 nm are observed, which are caused by the para-coupled branches growing from the phenazine-like structures.…”
Section: Uv-vis Resultsmentioning
confidence: 99%
“…16,18,30 The peak at 371 nm may also be contributed by phenazine. 31 Hence, from the UV-Vis and FTIR results, case (A) samples should be composed of the phenazine-like AN oligomers with some substituted quinones. 14,16,18,30 For case (B), the shape of the spectrum is similar to that obtained from case (A), except that a shifted band at 361 nm (from 371 nm) and a weak broad band B614 nm are observed, which are caused by the para-coupled branches growing from the phenazine-like structures.…”
Section: Uv-vis Resultsmentioning
confidence: 99%
“…A nitrogen (99.999%) purge was maintained while transferring the cuvette from the desiccator to the UV-visible spectrophotometer to minimize any contamination of surface acidity. Bailey and Karickhoff (1973) found that the presence of CO2 influenced the final surface acidity value, so care was taken to exclude CO2 as well as O2.…”
Section: Iron-bearing Minerals-indicator Filmsmentioning
confidence: 99%
“…The concept of employing molecular probes serving as indicators and UV-visible spectroscopy to investigate surface properties of mineral surfaces was proposed by Bailey and Karickhoff (1973) and Karickhoff and Bailey (1976). They investigated the interaction of various organic bases and basic pesticides with clay mineral surfaces, and monitored the protonation of these indicators of basic organic compounds at the mineral surfaces under varying water contents by UV-visible spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations